Navigation in virtual reality: Comparison of gaze-directed and pointing motion control - Christou, Chris; Tzanavari, Aimilia; Herakleous, Kyriakos; Poullis, Charalambos (My University, 2016)
We compared two locomotion techniques in an immersive CAVE-like display in order to determine which one promotes better performance in a wayfinding task. One method, commonly found in computer games, allows participants to steer through the 3D scene according to their gaze direction while the other uncouples the gaze direction from the direction of travel. In both cases tracked physical head movements determined the gaze direction. In order to provide a realistic scenario for comparing these methods we devised a task in which participants had to navigate to various houses of a virtual village that was previously seen on a map. The 2D coordinates of paths taken by participants were recorded together with their success rates in finding the targets, and the time taken to reach their destination. Participants showed better results with the pointing method of motion control, reaching the targets faster and with fewer errors. Results are interpreted with respect to the benefits afforded by large field of view displays.
Keywords: Motion control; Wayfinding; Navigation; Steering; Virtual reality